Same talk, different reaction? Communication, emergent leadership and gender. Issue 1 (29th October 2020) - Schlamp, Sofia; Gerpott, Fabiola H.; Voelpel, Sven C.
Abstract : Purpose: We investigate the role of gender in linking communicative acts that occur in the interactions of self-managed teams to emergent leadership. Specifically, this study presents a framework that differentiates between agentic and communal task- and relations-oriented communication as predictors of emergent leadership, and it hypothesizes that men and women do not differ in what they say but do differ in how they are rewarded (i.e. ascribed informal leadership responsibilities) for their statements. Design/methodology/approach: Interaction coding was used to capture the meeting communication of 116 members of 41 self-managed teams. Findings: Men and women exhibited the same amount of agentic and communal task- and relations-oriented communication and were equally likely to emerge as leaders. However, men experienced an emergent leadership advantage when engaging in agentic and communal task-oriented behaviors. Agentic and communal relations-oriented behaviors did not predict emergent leadership. Research limitations/implications: The findings imply that theories could be more precise in differentiating between objective behaviors (i.e. actor perspective) and perceptions thereof (i.e. observer perspective) to understand why women experience a disadvantage in assuming leadership roles. Practical implications: Although women displayed the same verbal behaviors as men, they experienced different consequences. Organizations can provide unconscious bias training programs, which help increase employees' self-awareness of a potential positive assessment bias toward men's communication. Originality/value: This research utilizes an innovative, fine-grained coding approach to gather data that add to previous studies showing that, unlike men, women experience a disadvantage in terms of emergent leadership ascriptions when they deviate from stereotypically expected behavior.